MiR-4668 as a Novel Potential Biomarker for Eosinophilic Esophagitis. (August 2020) - Bhardwaj, Neeti; Sena, Maria; Ghaffari, Gisoo; Ishmael, Faoud
Introduction: Eosinophilic esophagitis (EoE) is a clinico-pathological diagnosis characterized by esophageal dysfunction and eosinophilic infiltration of the esophagus. Demonstration of esophageal eosinophilia (more than 15 eosinophils/hpf) in biopsy specimen obtained by esophagogastroduodenoscopy (EGD) continues to be the gold standard for diagnosis and monitoring of response to therapy. There is a growing necessity for non-invasive biomarkers that can accurately diagnose this condition and assess response to therapy. While microRNAs (miRNA) are being investigated in allergic diseases, including EoE, not many studies have explored the role of salivary miRNAs in EoE. MiR-4668-5p is a particularly interesting candidate, as it is predicted to regulate TGF-beta signaling and has not previously been identified as a target in any allergy disease. We sought to further investigate the role of miR-4668 as a biomarker to characterize and monitor response to treatment with swallowed topical glucocorticoids. Methods: After IRB approval, twenty-two adult patients with EoE were randomly enrolled to provide a saliva sample before and after 2 months of swallowed fluticasone therapy. Differences of miRNA expression before and after treatment were analyzed by paired T-test. A significance cutoff of <0.05 was used for all analyses. Results: Expression of miR-4668 was higher in EoE vs. non-EoE subjects. The level of miR-4668 decreased in all subjects except one, with a mean fold change 0.49 ± 0.25. There was an association between miRNA expression and number of positive aeroallergens. The miR-4668 high group had a higher number of positive aeroallergen tests, while the miR-4668 low group had a greater number of subjects with drug allergies. Conclusions: In this study, we identified that salivary miRNAs may serve as biomarkers to characterize EoE and response to topical corticosteroids. We specifically identified miR-4668 as a novel potential biomarker, which was not previously discovered as a target in EoE or any other allergic disease.